2004
DOI: 10.1103/physrevb.70.012408
|View full text |Cite
|
Sign up to set email alerts
|

Rigid magnetic foam-like behavior in ball-milledFeAl

Abstract: After ball-milling nonmagnetic FeAl a grain structure resembling to a rigid magnetic foam is indicated by Mössbauer spectroscopy. It consists of nanosize nonmagnetic grains with ferromagnetic boundaries formed by about two atomic layers of Fe. The magnetic behavior is uncommon: (i) the transition to the paramagnetic state is glass-like and magnetic relaxation sets in at low temperatures; (ii) the magnitude of the local Fe magnetic moments decreases linearly with temperature; (iii) in high fields a strongly ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The presence of both the paramagnetic and ferromagnetic spectral components was attributed to nanosized nonmagnetic FeAl grains with ferromagnetic boundaries formed by about two atomic layers of Fe. The authors observed the dependence of the fraction of magnetic Fe atoms on the average grain size [31]. In the present work, the average size of the Fe(Al) nanograins remains fairly constant after 10, 20 and 30 h of mechanical alloying, whereas the fraction of the spectral ferromagnetic component increases with increasing the milling time and reaches 64% after 30 h of MA.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The presence of both the paramagnetic and ferromagnetic spectral components was attributed to nanosized nonmagnetic FeAl grains with ferromagnetic boundaries formed by about two atomic layers of Fe. The authors observed the dependence of the fraction of magnetic Fe atoms on the average grain size [31]. In the present work, the average size of the Fe(Al) nanograins remains fairly constant after 10, 20 and 30 h of mechanical alloying, whereas the fraction of the spectral ferromagnetic component increases with increasing the milling time and reaches 64% after 30 h of MA.…”
Section: Resultsmentioning
confidence: 69%
“…Therefore, both paramagnetic and weakly ferromagnetic regions of the Fe(Al) solid solution coexist in the alloy at room temperature. However, Kiss et al obtained similar Mössbauer spectra at 4.2 K after ball milling of the stoichiometric FeAl ingot [31]. The presence of both the paramagnetic and ferromagnetic spectral components was attributed to nanosized nonmagnetic FeAl grains with ferromagnetic boundaries formed by about two atomic layers of Fe.…”
Section: Resultsmentioning
confidence: 86%
“…Examining the grain size dependence of the fraction of the magnetic Fe atoms, p M (which is the spectral weight of the shaded area in Fig. 3a) it has been shown recently that the magnetic iron atoms mostly belong to grain boundaries in the ball-milled samples [5]. The average hf of the high-field part of the distribution, B m (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…the separation of the surface and bulk properties is not simple because they are influenced by impurities, mixing and disordering of the components [3,4]. In this paper the magnetic properties of ball-milled FeAl will be investigated, where a peculiar magnetic structure consisting of a nonmagnetic volume surrounded by a surface magnetic layer was found [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies [7][8][9][10][11][12] have concentrated on the Al rich end of the phase diagram and have reported the formation of fcc Al-Fe solid solutions which are paramagnetic at room temperature. On the Fe rich side, the behaviour near the equiatomic composition [13][14][15][16][17] and the structural and magnetic properties of specific compositions [18][19][20][21][22][23][24][25] as well as a range of compositions [3,[26][27][28] have been investigated. However, most of these studies report results of systems in which the alloying process is complete.…”
Section: Introductionmentioning
confidence: 99%